Young father-child relationship pattern and nutrition status among under-five children in Jember Regency, Indonesia - Ubaidillah Utsman; Tantut Susanto; Hanny Rasni; Nuning Dwi Merina; Fahruddin Kurdi (Journal of Community Empowerment for Health, 2022)
The younger age of fathers will affect the pattern of relationship between fathers and their children, particularly in terms of nutrition provision of children under five years. The objective of this study was to identify and measure the correlation between the pattern of relationship between fathers and their children and nutritional status in Jember Regency of Indonesia. A cross-sectional study was conducted from September to December 2019. The participants were 39 young fathers aged 17-19 years who have an infant aged 0-5 years. They were recruited using total sampling technique. Respondents’ characteristics and child-parent relationships were measured using a questionnaire. The Chi-square test was used to analyze the data. Among the 39 young fathers, the young father and children relationship was high (56.4%). Meanwhile, the nutritional status of children was good (48.7%). Furthermore, there was a significant correlation between the pattern of father-child relationship and nutritional status among the children (χ2= 11.83; p<0.001). The higher the pattern of father-child relationship, the better was the nutrition of the children (OR= 12.0; 95% CI= 2.5-57.4). The father-child relationship pattern is related to children’s nutritional status. Therefore, the fatherchild relationship should be well-maintained to fulfill the nutrition needs of under-five children.